Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s10854-011-0606-4
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural evolutions of the Ag nano-particle reinforced SnBiCu-xAg/Cu solder joints during liquid aging

Abstract: Ag nano-particle reinforced Sn30Bi0.5Cu-xAg (x = 1 wt%, 2 wt% and 5 wt%) solder pastes were prepared and reflowed on Cu substrates at 523 K. Then, the solder joints were liquid aged at 473 K for 6 and 12 h. Microstructural evolutions of these solder joints were observed by scanning electron microscopy (SEM). The results show that Bi-rich phase was refined in the as-reflowed Sn30Bi0.5Cu-xAg composite solder matrices. With the increase of the liquid aging time, Bi-rich phase was refined both in the Sn30Bi0.5Cu s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…7), the increasing layer thickness with decreasing silver content can be explained by the following. The Ag 3 Sn intermetallic compounds can adsorb on the surface of the Cu 6 Sn 5 intermetallic layer, and they can obstruct the growing of that layer in agreement with [24,25]. If the silver content in the solder is higher -especially in the case of alloys with hypereutectic silver compositions (>2.7 wt%) -more Ag 3 Sn IMC can adsorb and thus lower intermetallic layer can form.…”
Section: Discussionmentioning
confidence: 99%
“…7), the increasing layer thickness with decreasing silver content can be explained by the following. The Ag 3 Sn intermetallic compounds can adsorb on the surface of the Cu 6 Sn 5 intermetallic layer, and they can obstruct the growing of that layer in agreement with [24,25]. If the silver content in the solder is higher -especially in the case of alloys with hypereutectic silver compositions (>2.7 wt%) -more Ag 3 Sn IMC can adsorb and thus lower intermetallic layer can form.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the development of composite lead-free solders by mechanically adding micro/nano-sized particles into Sn-based lead-free solder matrices enhances their wettability and mechanical properties [17]. Metallic micro/nano-sized alloys of elements such as silver, copper, nickel, antimony, and bismuth improve the mechanical properties of a lead-free solder, and simultaneously reduce the melting point.…”
Section: Introductionmentioning
confidence: 99%